2023
DOI: 10.1097/hep.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

The global fatty liver disease Sustainable Development Goal country score for 195 countries and territories

Abstract: Background and Aims: Fatty liver disease is highly prevalent, resulting in overarching wellbeing and economic costs. Addressing it requires comprehensive and coordinated multisectoral action. We developed a fatty liver disease Sustainable Development Goal (SDG) country score to provide insights into country-level preparedness to address fatty liver disease through a whole-of-society lens. Approach and Results: We developed 2 fatty liver disease–SDG scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Diabetes is the familiar metabolic disorders where the counting of humans enduring from the disorder is escalating across the globe (GBD 2021Diabetes Collaborators, 2023Park & Jang, 2017), often associated with obesity, the condition can elevate the risk of diabetic kidney failure, cardiovascular disorder, retinal disease, and artery disease (Lazarus et al, 2023;Mukherjee et al, 2020). β-sitosterol has also been extensively researched for its role in regulating cholesterol and blood glucose levels, numerous studies have demonstrated that β-sitosterol effectively lowers LDL cholesterol by inhibiting its absorption in the intestines (Wu et al, 2022); moreover, it has been shown…”
Section: Effects On Metabolic Disordersmentioning
confidence: 99%
“…Diabetes is the familiar metabolic disorders where the counting of humans enduring from the disorder is escalating across the globe (GBD 2021Diabetes Collaborators, 2023Park & Jang, 2017), often associated with obesity, the condition can elevate the risk of diabetic kidney failure, cardiovascular disorder, retinal disease, and artery disease (Lazarus et al, 2023;Mukherjee et al, 2020). β-sitosterol has also been extensively researched for its role in regulating cholesterol and blood glucose levels, numerous studies have demonstrated that β-sitosterol effectively lowers LDL cholesterol by inhibiting its absorption in the intestines (Wu et al, 2022); moreover, it has been shown…”
Section: Effects On Metabolic Disordersmentioning
confidence: 99%
“…Fatty liver disease represents a contemporary public health challenge that requires multidisciplinary and multisectoral responses and novel collaboration, from re-orienting health systems to addressing food systems, the built environment, and social deprivation 14 . For policymakers, practitioners, industry, and patient advocates, this represents unique challenges as they seek to embrace the complexity and scale of the problem with the need for effective and efficient responses 15 . Building on earlier work, this study engaged a global multidisciplinary group of experts to develop a set of consensus actions, which can collectively turn the tide on this silent but challenging public health threat.…”
Section: Introductionmentioning
confidence: 99%
“…[14] For policymakers, practitioners, industry, and patient advocates, this represents unique challenges as they seek to embrace the complexity and scale of the problem with the need for effective and efficient responses. [15] Building on earlier work, this study engaged a global multidisciplinary group of experts to develop a set of consensus actions, which can collectively turn the tide on this silent but challenging public health threat.…”
Section: Introductionmentioning
confidence: 99%